Outcome of Infants with Hypoxic-Ischemic Encephalopathy Treated by Whole Body Cooling and Magnesium Sulfate - Abdel-Aziz, Safwat M.; Rahman, Mohamed Sabry M. Abdel; Shoreit, Asmaa H.; Din, Moustafa Ez El; Hamed, Enas A.; Gad, Eman Fathalla (Journal of Child Science, 2021)
Therapeutic hypothermia (TH) either by selective head cooling or whole-body cooling decreases brain damage and provide neuroprotection and reduced mortality rate in cases of moderate-to-severe hypoxia-ischemia encephalopathy (HIE) of newborns, especially if started at first 6 hours after birth. Also, management with adjuvant therapies like magnesium sulfate (MS) provides more neuroprotection. The interventional randomized controlled research aimed to assess short-term actions of TH as sole therapy and in combination with MS as a neuroprotective agent for the treatment of HIE newborn infants. A total of 36 full-terms and near-term infants delivered at Assiut University Children's Hospital and fulfilled HIE criteria were enrolled. They were divided equally into three groups; Group 1 (n = 12) received whole body cooling during first 6 hours of life as a sole therapy; Group 2 (n = 12) received whole body cooling in addition to MS as adjuvant therapy; Group 3 (n = 12) received supportive intensive care measures as a control. TH plus MS group (group 2) had a significantly good short-term outcomes as short period of respiratory support and mechanical ventilation (p-value =0.001), less in incidence of convulsion (p-value = 0.001) and early in feeding initiation (p-value = 0.009), compared with other groups managed by TH (group 1) or by supportive treatment (group 3). In conclusion, whole body cooling in addition to MS as adjunctive therapy for the treatment of HIE neonates is safe therapy that improves short-term outcome both clinically and radiologically.
Keywords: hypoxic-ischemic encephalopathy; magnesium sulfate; neuroprotective; therapeutic hypothermia